Drivers and barriers for the adoption to the circular economy by organic food producers in short chains - Pasqualotto, Carina (2023)
The world faces a current problem with the economic and food crisis, environmental pollution, increased extraction of materials, continuous reduction of non-renewable resources, added to the continuous increase in the global population. Adherence to the Circular Economy (CE), cultivation of organic products, and the sale of these products through short circuits, makes it possible to develop more sustainable alternatives of production and consumption, and can be considered a way toward sustainable development. In this sense, this study aimed to identify drivers and barriers for the adoption of  CE by organic food producers in short chains. Based on a systematic review of the preliminary literature, a qualitative research was developed with in-depth interviews with experts. As result, the study presented the drivers and barriers for the adoption of CE by organic food producers in short chains. The study has also shown that the Short Organic Food Chains  (SOFC) are integrated with the concepts of CE , and are moving toward common sustainability objectives, demonstrating high potential for the exploration and development of CE  in the SOFC context.